2015
DOI: 10.5194/acp-15-4279-2015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the feedback between aerosol and meteorological variables in the atmospheric boundary layer during a severe fog–haze event over the North China Plain

Abstract: Abstract. The feedback between aerosol and meteorological variables in the atmospheric boundary layer over the North China Plain (NCP) is analyzed by conducting numerical experiments with and without the aerosol direct and indirect effects via a coupled meteorology and aerosol/chemistry model (WRF-Chem). The numerical experiments are performed for the period of 2–26 January 2013, during which a severe fog–haze event (10–15 January 2013) occurred, with the simulated maximum hourly surface PM2.5 concentration of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
148
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(173 citation statements)
references
References 56 publications
15
148
3
Order By: Relevance
“…These haze layers could spread across northern and eastern China and persist over a week during autumn and winter, inducing elevated PM 2.5 concentration exceeding 500 μg m −3 and instantaneous visibility degradation to less than 200 m Li, Zhou et al, 2011). The tremendous aerosol loading arising from frequent haze events exerted a profound impact on the radiation balance and weather in eastern China (Liang and Xia, 2005;Liu et al, 2007;Gao et al, 2015). Nevertheless, the radiation feedbacks between anthropogenic aerosols and atmospheric chemistry during haze events have rarely been intensively resolved, which are expected to be significant in the vicinity of major cities.…”
Section: Wrf-chem Model Descriptionsmentioning
confidence: 99%
“…These haze layers could spread across northern and eastern China and persist over a week during autumn and winter, inducing elevated PM 2.5 concentration exceeding 500 μg m −3 and instantaneous visibility degradation to less than 200 m Li, Zhou et al, 2011). The tremendous aerosol loading arising from frequent haze events exerted a profound impact on the radiation balance and weather in eastern China (Liang and Xia, 2005;Liu et al, 2007;Gao et al, 2015). Nevertheless, the radiation feedbacks between anthropogenic aerosols and atmospheric chemistry during haze events have rarely been intensively resolved, which are expected to be significant in the vicinity of major cities.…”
Section: Wrf-chem Model Descriptionsmentioning
confidence: 99%
“…As aforementioned, haze pollution generally occurred at regional scale in East and North China. Previous studies have highlighted the importance of aerosol-PBL interaction in cities (Petaja et al, 2016;Wang et al, 2014a;Gao et al, 2015b;Cai et al, 2017;Li et al, 2017b). It is noteworthy that more than half of the population live in the rural area with a majority in the plain areas in the North and Central China, who also has been exposed to fine particulate pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The model results from Gao et al (2015) showed that during the fog and haze mixed event over the North China Plain, aerosols led to a significant negative radiation forcing at the surface and a large positive radiation forcing in the atmosphere and induced significant changes in meteorological variables in daytime. As a result, the atmosphere was much more stable and thus the surface wind speed decreased and the PBL height decreased.…”
Section: Introductionmentioning
confidence: 99%